КРИТЕРИИ ПРОГНОЗИРОВАНИЯ СЕРДЕЧНО-СОСУДИСТЫХ ЗАБОЛЕВАНИЙ У ДЕТЕЙ, ПРОЖИВАЮЩИХ в ПРИАРАЛЬе - Ахмедова, Дилором Ильхамовна; Ахмедова, Нилюфар Расуловна; Жиемуратова, Гулпаршын Кошкинбаевна (Медицина: теория и практика, 2020)